Applications in remote sensing and environmental analysis: Digital geomorphometric characterization of the relief in Ribeirão das Cruzes Watershed, Selvíria / MS (Brazil) - Santori, Alisson Rodrigues; Garcia, Patricia Helena Mirandola; Stevaux, José Candido (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
The present study aims to describe the morphologic and geographic structuring and report a relief morphometric analysis in a cutout of the environmental planning. To do so, geoprocessing techniques were widely used and supported by systemic theory. The main objective is to process relief data in Geographic Information System (GIS) and contribute to the database of characteristics from different local geomorphometric variables. Thus, the theorical basis of the research suggests the use of General System Theory based on their concepts to understand the morphologic structure of the relief at different levels, also the condition of the relief shapes and their classification. This case study occurs methodologically, defining the relief category as an environmental component of direct and vital interaction with other resources and dynamic components, considering mainly the whole environmental system. In this study, the environmental system is the Sucuriú River watershed. Therefore, to get the environmental analysis of the relief, the methodology consists of pre-processing and processing of digital land modeling data based on Synthetic Aperture Radar (SAR) records. Those can obtain different characteristics by using the methodology of geomorphometric variables extraction, which are the set of variables subject to land measuring. The results should cartographically reveal the dynamics and structural morphology of the relief, observing important parameters of relief configuration and concluding with the presentation and correlation of the relief shapes dynamics in all the considered environmental system.